Normative Construction of Obligations to Balance the Parenting Roles By Working Partners in Gender Equality Perspective - Irma Nur Rahmy; Yudi Hamsah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
One contemporary issue in family law today concerns the division of responsibilities between parents who both have jobs, particularly in balancing their roles in child rearing. The normative construction of the duty to balance parenting roles between working couples, viewed from the perspective of gender equality, needs to be addressed. The purpose of this research is to formulate normative provisions regarding the duty of balancing childcare responsibilities by working couples. This study adopts a library research method with an interdisciplinary approach, examining the problem from various perspectives, including law and gender. The research results indicate that the formulation of normative duties in childcare is not entirely adequate in protecting the rights of the child. This inadequacy leads to gender injustice, specifically the double burden placed on women. The gender injustice is also caused by the absence of clear and explicit legal provisions regulating the balancing of childcare roles by working couples. Therefore, it is proposed that the balancing of childcare roles be implemented by amending Article 45 of Law No. 1 of 1974 concerning marriage, incorporating language that mandates the duty of balancing childcare roles by working couples.